Additive Effect of Diesel Exhaust Particulates and Ozone on Airway Hyperresponsiveness and Inflammation in a Mouse Model of Asthma - Jang, An-Soo (The Korean Academy of Medical Sciences, 2005)
Allergic airway diseases are related to exposure to atmospheric pollutants, which have been suggested to be one factor in the increasing prevalence of asthma. Little is known about the effect of ozone and diesel exhaust particulates (DEP) on the development or aggravation of asthma. We have used a mouse asthma model to determine the effect of ozone and DEP on airway hyperresponsiveness and inflammation. Methacholine enhanced pause (P(enh)) was measured. Levels of IL-4 and IFN-γ were quantified in bronchoalveolar lavage fluids by enzyme immunoassays. The OVA-sensitized-challenged and ozone and DEP exposure group had higher P(enh) than the OVA-sensitized-challenged group and the OVA-sensitized-challenged and DEP exposure group, and the OVA-sensitized-challenged and ozone exposure group. Levels of IFN-γ were decreased in the OVA-sensitized-challenged and DEP exposure group and the OVA-sensitized-challenged and ozone and DEP exposure group compared to the OVA-sensitized-challenged and ozone exposure group. Levels of IL-4 were increased in the OVA-sensitized-challenged and ozone exposure group and the OVA-sensitized-challenged and DEP exposure group, and the OVA-sensitized-challenged and ozone and DEP exposure group compared to OVA-sensitized-challenged group. Co-exposure of ozone and DEP has additive effect on airway hyperresponsiveness by modulation of IL-4 and IFN-γ suggesting that DEP amplify Th2 immune response.